A collaborative study to establish the national standard for SARS-CoV-2 RNA nucleic acid amplification techniques (NAAT) in Taiwan. (September 2022) - Lin, Po-Lin; Wu, Ming-Sian; Wu, Po-Chi; Chen, Hsin-Mei; Peng, Yi-Hsuan; Hsu, Jia-Chuan; Wang, Der-Yuan
Abstract: The conventional PCR remains a valuable method to detect the newly emergent coronavirus rapidly and accurately. Our investigation aimed to establish the standard materials of SARS-CoV-2 for NAAT detection. We provided formalin-inactivated SARS-CoV-2 and confirmed RNA copy numbers. In addition, the virus genome was confirmed with whole-genome sequencing and identified as Wuhan/WI04/2019. Seven laboratories were invited for this collaborative study, according to the reporting data, we determined the SARS-CoV-2 with the unit of 6.35 Log10 copies/mL as the national standard. The availability of the national standard (NS) of SARS-CoV-2 will facilitate the standardization and harmonization of SARS-CoV-2 NAAT assays.